Pengembangan Kulit Manis Mendukung Pembangunan Pertanian Kerinci - Firdaus, Firdaus; Izhar, Lutfi; Salwati, Salwati (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2022)
Cinnamon is one of leading plantation commodity in Jambi Province, especially in Kerinci Regency, and has an enormous portion as the country's revenue. In addition, cinnamon is a multi-functional plant that can be used in industry, besides functioning as land conservation. However, seed support and technology studies need to be more considered and implemented. The purpose of this paper was to describe the seeds and cultivation innovation technology for cinnamon in Jambi Province. The study was carried out in several sub-districts in Karinci in 2018, using selected mother trees, demonstration plot for harvest and post-harvest analysis. The results show that recently the need for cinnamon seeds still has not sufficient. However, more than 4.000 cinnamon seeds have been distributed and provided with technology assistance for local Kerinci farmers. Dissemination of institutional cinnamon production guidelines and certification of cinnamon seedlings has been carried out in several farmers. The package of cinnamon technology components has been studied and disseminated within this Kerinci areas.